POPULATION GROWTH IN THE YOGA-ORIENTED LIFE PATH OF WOMEN: A SOCIAL PROBLEM - Sidhu, Sandeep; Gautam, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In today’s modern era, it is very difficult to live a healthy and happy life. We have created this difficulty ourselves. This difficulty is standing in front of us in the form of overpopulation. Today this problem has taken such a terrible form that man has to struggle for health and happiness. A very advanced path to health and happiness was given to us by our ancient sages, this path is the path of ’Yoga’. But in today’s crowded environment where there is pollution and plunder of resources all around, it is very difficult to live a yoga-oriented life. Due to population growth, man is busy in collecting resources throughout his life, due to which he is not able to take out time for his body and mind. Population growth is a very big problem, due to which a woman spends her entire life in fulfilling the needs of the family. Due to which she is not able to take out time for yoga and she remains unhealthy and surrounded by sorrow throughout her life. Due to this, women live their life in a painful manner. Pure environment and peace is required for yoga, but due to population growth, the environment is impure and there is unrest all around. Due to this, it is very difficult for women to live a life full of yoga in today’s era. We can say that population growth is a big social problem in the path of women’s life. Through yoga, both body and mind remain healthy together. In yoga, the body becomes flexible and strong through asanas. The body becomes light, balanced and all activities are regular through pranayam. Tolerance comes through mudras and bandhas. According to (Chandrashekhar 2018, p. 63), it can be easy for women to adopt yoga programs in their daily lives and like exercise, yoga also has a very positive effect on the daily lives of women. According to (Ekta 2003, p. 15-30), we can adopt yoga in our lives to make the body healthy and efficient, because more benefits can be gained by adopting yoga.